Karnataka land grabbing prohibition act, 2011: Karnataka act no. 38 of 2014 - Puliani, Yashpal (Bangalore Karnataka law journal publications, 2023)
Karnataka act: as amended by act no. 30 of 2022
Keywords: Karnataka act